Investigating the Emission Mechanism in the Spatially Resolved Jets of Two z ≈ 3 Radio-loud Quasars - Jaya Maithil; Daniel A. Schwartz; Aneta Siemiginowska; Preeti Kharb; Diana M. Worrall; John F. C. Wardle; Giulia Migliori; Chi C. Cheung; Bradford Snios; Doug B. Gobeille; Herman L. Marshall; Mark Birkinshaw (The Astrophysical Journal)
This study focuses on high-redshift, z > 3, quasars where resolved X-ray jets remain underexplored in comparison to nearby sources. Building upon previous work, we identify and confirm extended kiloparsec-scale jets emission in two quasars (J1405+0415, z = 3.215; J1610+1811, z = 3.122) through meticulous analysis of Chandra X-ray data. To deepen our understanding, high-resolution radio follow-up observations were conducted to constrain relativistic parameters, providing valuable insights into the enthalpy flux of these high-redshift active galactic nucleus jets. The investigation specifically aims to test the X-ray emission mechanism in these quasars by exploring the inverse Compton scattering of cosmic microwave background photons by synchrotron-emitting electrons. Our novel method uses a prior to make a Bayesian estimate of the unknown angle of the jet to our line of sight, thus breaking the usual degeneracy of the bulk Lorentz factor and the Doppler beaming factor.